Pengaruh Job Crafting terhadap Kinerja Karyawan dengan Work Engagement sebagai Variabel Mediasi: Studi Kasus pada Karyawan Percetakan di Kota Samarinda - Muhammad Said; Dirga Lestari AS (Indo Publishing, 2026)
This study aims to analyze the influence of job crafting on employee performance with work engagement as a mediating variable among printing industry employees in Samarinda City. The creative economy in Indonesia, particularly the printing industry, has undergone significant transformation due to digital technology advancements. This research employs a quantitative approach with an explanatory design. Data were collected through questionnaires from 140 printing employees selected using purposive sampling. The analysis was conducted using Structural Equation Modeling with SmartPLS 4. The results indicate that job crafting has a positive and significant effect on employee performance (coefficient 0.363; p-value 0.000). Job crafting also has a positive and significant effect on work engagement (coefficient 0.806; p-value 0.000). Work engagement has a positive and significant effect on employee performance (coefficient 0.599; p-value 0.000). Furthermore, work engagement mediates the relationship between job crafting and employee performance (indirect effect 0.483; p-value 0.000). The R² of 0.841 indicates that 84.1% of employee performance variation is explained by job crafting and work engagement. These findings provide implications for printing business owners to provide space for job crafting and create a supportive work environment to enhance engagement and performance.